2010
DOI: 10.1681/asn.2009030307
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Renin Secretion by Angiotensin II Blockade is Gsα-Dependent

Abstract: Angiotensin II converting enzyme inhibitors (ACEI) or angiotensin II receptor blockers (ARB) presumably stimulate renin secretion by interrupting angiotensin II feedback inhibition. The increase in cytosolic calcium caused by activation of Gq-coupled AT1 receptors may mediate the renin-inhibitory effect of angiotensin II at the cellular level, implying that ACEI and ARB may work by reducing intracellular calcium. Here, we investigated whether angiotensin II blockade acts predominantly through Gs-mediated stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 35 publications
1
33
1
Order By: Relevance
“…We used pharmacological and genetic approaches to block the ang II effects and found that enhCRE and CNRE are not involved in the transactivation of human renin gene under these conditions. The partial discrepancy of our results with the earlier data [4] implies that the cAMP/PKA cascade (and particularly the human renin cAMP target sequences) may be critical for the regulation of renin expression by low-salt diet rather than by ang II (see also below). Alternatively, a range of in vitro and in vivo studies strongly suggest that mouse and human renin genes are not controlled through completely identical molecular mechanisms [11,19,34,40].…”
Section: Renincontrasting
confidence: 98%
See 1 more Smart Citation
“…We used pharmacological and genetic approaches to block the ang II effects and found that enhCRE and CNRE are not involved in the transactivation of human renin gene under these conditions. The partial discrepancy of our results with the earlier data [4] implies that the cAMP/PKA cascade (and particularly the human renin cAMP target sequences) may be critical for the regulation of renin expression by low-salt diet rather than by ang II (see also below). Alternatively, a range of in vitro and in vivo studies strongly suggest that mouse and human renin genes are not controlled through completely identical molecular mechanisms [11,19,34,40].…”
Section: Renincontrasting
confidence: 98%
“…Ang II influences renin expression by a dual mechanism, including a direct action on the JG cells through Agt1r receptors and a modulation of the vascular tone that increases peripheral resistance and thus arterial pressure [2]. In addition, cAMP signaling was recently found to be crucial for the stimulation of mouse renin release by ang II blockade combined with low-salt diet [4]. We used pharmacological and genetic approaches to block the ang II effects and found that enhCRE and CNRE are not involved in the transactivation of human renin gene under these conditions.…”
Section: Reninmentioning
confidence: 99%
“…The latter model has been widely used for the conditional inactivation of different genes expressed in the renin-secreting granular cells of the juxtaglomerular apparatus in the kidney. [21][22][23][24][25][26][27][28][29] These studies showed that, at the whole-organ level, the Ren1 d Cre is strongly expressed in the kidney, whereas in other tested tissues, the Cre expression was at or near background levels. 24 Nota bene, clearly, however, these results did not exclude that there might be minor populations of Cre-expressing cells in other tissues as well.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cause of its progression is multifactorial, [1][2][3] activation of the renin-angiotensin-aldosterone system (RAAS) is a key effector and RAAS inhibitors are among the beststudied renoprotective agents. 4 -7 Although the RAAS is complex, with new peptides such as angiotensin 1-7 and angiotensin IV exhibiting profibrotic effects by binding to specific receptors as well as observations that aldosterone and even renin itself can stimulate fibrogenesis in the kidney, 8 -12 and angiotensin II (Ang II) blockade can stimulate renin release, 13 the review presented here focuses exclusively on Ang II as the major component of the RAAS effect on morphogenesis. There are several excellent reviews covering the other components of the RAAS and their profibrotic actions in the kidney.…”
mentioning
confidence: 99%